Attachment to mother and attachment to peers in adolescence: The mediating role of self-esteem | Vinculação à mãe e ligação aos pares na adolescência: O papel mediador da auto-estima - M. Rocha (2011)
According to attachment theory, the quality of relationships with parental figures play a key role in the way young people perceive themselves and others, contributing also to self-esteem development of to the relational ties built with peers. The main purpose of this study is to evaluate the contribution of the quality of attachment to mother in the prediction of the construction of peers bonds, taking into account the hypothesis of the mediating role of self-esteem, in a sample of 742 adolescents from both sexes, between 13 and 23 years (M=17.09, SD=1.84), from intact and divorced families. The study used the Attachment Questionnaire to the Father and Mother (Matos & Costa, 2004), the Inventory of Parental and Peer Attachment (Armsden & Greenberg, 1987) and also the Rosenberg's Self-Esteem Scale (Rosenberg, 1965). All questionnaires presented appropriate psychometric qualities, with good internal consistency and adequate fit indexes (1st order confirmatory factor analysis). Results were obtained through structural equations methodology, and are indicative of quality of attachment to the mother as direct and indirect predictor of the quality of peers' relationships. In the model tested, self-esteem is positively predicted by the mother's quality of emotional bond, and negatively by inhibition of exploration and individuality and separation anxiety. The results are also consistent with the mediating role of self-esteem on the association between quality of attachment to mother and attachment to peers.